High oxygen consumption rates in the deep layers of the North Aegean Sea (eastern Mediterranean) - SOUVERMEZOGLOU, E.; KRASAKOPOULOU, E. (Mediterranean Marine Science, 2002)
Severe winter meteorological conditions promote dense water formation over the shelves of the North Aegean Sea. The newly formed dense water fills the deep basins of the North Aegean Sea, contributing to their ventilation and the downward transport of organic and inorganic material. The great bathymetric variability imposes limitations on the deep circulation and the communication between the various basins and makes the North Aegean Sea an appropriate area for the monitoring of oxygen consumption in the deep layers. Historical hydrographic data suggest that there was extensive production of dense water in the North Aegean Sea on two occasions during the last decade, the winters of 1987 and 1992-1993. Our data series from August 1986 to September 1989 and from March 1997 to February 1999, permitted us to follow, step by step, the oxygen consumption and the nutrient regeneration in the deep basins of the northern Aegean Sea during these periods of isolation. The organic matter reaching the bottom layer just after the deep water formation event is rich in labile and easily oxidizable material and its decomposition leads to a significant oxygen uptake during the first year of stagnation. The further decomposition of the remaining semi-labile and refractory material turns over on greater time scales, by consuming lesser amounts of oxygen. A more significant oxygen decrease is recorded in the eastern basin (Lemnos Basin) of the North Aegean Trough, than in the central (Athos Basin) and the western (North Sporades Basin) ones and is attributed to the irregular contribution of the Black Sea Water (BSW) to the water masses formed on the different shelves of the North Aegean Sea. Our results and the existing data on the Turkish straits showed that dissolved organic matter is the major constituent responsible for this high oxygen consumption. The slightly different particulate organic carbon fluxes to these depressions play a secondary role.